A cross-linked hydrophilic coating magnetic microsphere and its preparation method and application
By covering the surface of the magnetic microspheres with silicon oxide functional coating and forming a crosslinked coating, the shortcomings of magnetic microspheres in mechanical stability and magnetic responsiveness are solved, and higher chemical stability and detection sensitivity are achieved, which are suitable for a variety of biological applications.
Patent Information
- Application Number
- CN202510058597.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The prior art is difficult to effectively ensure mechanical stability, superparamagnetic responsiveness, surface coating functionality and stability on micro-nano-scale magnetic microspheres, especially in the loss and loss of magnetic substances.
By covering the surface of the magnetic polymer-based sphere with a silicon oxide functional coating and forming a crosslinking coating through the crosslinking reaction of the epoxy group and the thiol group, the overall structural stability and biocoupling function of the magnetic microspheres are ensured.
It improves the chemical stability and environmental hydrophilic properties of magnetic microspheres, reduces non-specific adsorption of proteins, enhances magnetic response time and detection sensitivity, and is suitable for biological applications such as cell isolation, protein isolation and purification.
Smart Images

Figure CN119455921B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of micro-nano materials, and in particular to a cross-linked hydrophilic coating magnetic microsphere and a preparation method and application thereof. Background Art
[0002] Micron-sized magnetic microspheres have attracted extensive attention in the field of chemiluminescent immunoassays due to their superparamagnetism, monodispersity, chemical environment stability, etc. At the same time, due to their active surface functionality, they can be effectively coupled with bioactive ligands and are an important carrier for medical and molecular biology research.
[0003] Yuan Dingzhong et al. synthesized magnetic fluid in advance, dispersed the magnetic fluid evenly into oil-soluble monomers and initiators, and successfully prepared P(St / MAA) magnetic microspheres using dispersed polymers. They also investigated specific influencing factors and found the optimal conditions for the internal structure of the magnetic microspheres and the content of surface carboxyl groups. This scheme synthesized magnetic microspheres with carboxyl groups (-COOH) on the surface by a relatively simple method, but it could not guarantee their effective magnetism. Only weakly magnetic microspheres could be obtained by embedding magnetic fluids, which limited their application (Yuan Dingzhong et al. Journal of Materials Science & Engineering. 2008(3). 342).
[0004] CN105288731A discloses a method for preparing a biomimetic coating by crosslinking a thiol group with an epoxy group, which mainly uses a vinyl monomer containing a phosphorylcholine group and a vinyl monomer containing an epoxy group to perform a polymerization reaction to obtain a phospholipid choline polymer containing an epoxy group, and then dissolves the phospholipid choline polymer containing an epoxy group in a solvent to obtain a polymer solution, then adds a polymer solution to a polythiol to obtain a mixed solution, and finally applies the mixed solution to the surface of the material to be modified, immerses it in distilled water after drying, and obtains a biomimetic coating crosslinked with an epoxy group and a thiol group, and the biomimetic coating has good hydrophilicity and stability. However, the epoxy group in the patent is provided by a vinyl monomer and a polymerization reaction is performed to modify the epoxy group on the surface of the microsphere, but the surface configuration of the epoxy group caused by the polymerization reaction is difficult to control, and the number of epoxy groups is extremely low.
[0005] CN117417575A discloses a low-luminescence background polymer magnetic sphere material and its preparation method, and the preparation method comprises the following steps: using polystyrene as seed sphere and glycidyl methacrylate as monomer, using seed swelling method to prepare GMA porous sphere, performing amination after solvent extraction to obtain amination GMA porous sphere; generating magnetic nanoparticles in situ on the surface of amination GMA porous sphere, and ball milling after drying to obtain magnetic microspheres; coating the magnetic microspheres with silica gel and silanization, and then grafting organic monomers to form a coating layer to obtain low-luminescence background polymer magnetic spheres. Ball milling and coating with a coating layer make the magnetic nanoparticles uniformly and stably distributed on the surface of the microspheres, so that the magnetic response intensity and dispersibility are good.
[0006] Therefore, for micro- and nano-scale magnetic microspheres, it is of great significance to ensure their mechanical stability, superparamagnetic responsiveness, and surface coating functionality and stability. Summary of the invention
[0007] The invention provides a cross-linked hydrophilic coating magnetic microsphere and a preparation method and application thereof.
[0008] The specific technical solutions are as follows:
[0009] The first invention of the present invention protects a cross-linked hydrophilic coated magnetic microsphere, comprising:
[0010] A magnetic polymer-based ball, comprising a polymer core and a magnetic material coated on the outer surface of the polymer core;
[0011] A silicon oxide functional coating is coated on the outer surface of the magnetic polymer-based ball, wherein the raw materials of the silicon oxide functional coating include organic silicate and epoxy compound;
[0012] A cross-linked coating is coated on the outer surface of the silicon oxide functional coating, and the raw material of the cross-linked coating includes mercapto acid.
[0013] In the cross-linked hydrophilic coated magnetic microspheres of the present application, the organic silicate is bonded to the hydroxyl group in the magnetic material to form silanol group, and the alkoxy group in the epoxy compound is bonded to the silanol group, so that the silicon oxide functional coating is coated on the outer surface of the magnetic polymer-based ball; the mercapto group in the mercapto acid is bonded to the epoxy group of the epoxy compound, so that the cross-linked coating is coated on the outer surface of the silicon oxide functional coating.
[0014] The present invention is based on a magnetic polymer-based ball, and a silicon oxide functional coating is coated on its surface, which can not only effectively prevent the loss and loss of magnetic materials in the subsequent modification process, but also provide a basis for the subsequent cross-linked coating; the outer surface of the silicon oxide functional coating is coated with a cross-linked coating formed by cross-linking of epoxy and thiol groups, which further ensures the overall structural stability of the magnetic microspheres and also provides a basis for the subsequent biological coupling functional groups. The present invention utilizes the "click chemistry-like characteristics" of epoxy and thiol reactions, such as fast reaction speed, mild conditions, and high selectivity, and can effectively wrap and coat the surface of the magnetic polymer-based ball without any auxiliary conditions. In addition, the epoxy and thiol reactions produce secondary products hydroxyl and thioether, which greatly improve the chemical stability and environmental hydrophilicity of the magnetic polymer-based ball, effectively reduce the nonspecific adsorption of proteins by the cross-linked hydrophilic coating magnetic microspheres, and improve the sensitivity, providing a new exploration direction for the cross-linked hydrophilic coating magnetic microspheres. The invention relates to a method for producing a cross-linked hydrophilic coated magnetic microsphere having simple and readily available raw materials, low cost and convenient industrial conversion. The obtained cross-linked hydrophilic coated magnetic microsphere can be used as a biological raw material in the fields of cell separation, protein separation and purification, immobilized enzyme, immunoassay, targeted drug, DNA separation and nucleic acid hybridization.
[0015] In some embodiments, the thickness of the cross-linked coating is 10 to 500 nm, preferably 10 to 100 nm.
[0016] In certain embodiments, the mercapto acid is selected from one or two of mercaptopropionic acid, 2,3-dimercaptobutyric acid, 2,3-dimercaptosuccinic acid and 6,8-dimercaptooctanoic acid. Preferably, it is dimercapto acids, such as 2,3-dimercaptosuccinic acid and 6,8-dimercaptooctanoic acid. The present application uses mercapto acid as a small molecule chain extender (or cross-linking agent). Only by using difunctional or more mercapto acids can an effective coating be formed, otherwise it is only a simple surface modification that cannot be effectively coated. In addition, the present application utilizes the mercapto group in the mercapto acid and the epoxy group contained in the silicon oxide functional coating to generate a secondary product thioether, and a phase change from hydrophobic to hydrophilic occurs, so that the cross-linked hydrophilic coating magnetic microspheres have hydrophilic properties.
[0017] In certain embodiments, the mass ratio of the magnetic polymer-based spheres to the mercapto acid is 1:(0.5-20).
[0018] In some specific embodiments, the mass ratio can be 1:(0.5-3), 1:(2-13), or 1:(10-20). In one example, it is 10:8 or 10:5.
[0019] In some embodiments, the thickness of the silicon oxide functional coating is 10 to 300 nm, more preferably 10 to 100 nm. The surface of the silicon oxide functional coating in the present application has a large number of abundant silanol and epoxy groups, which are provided by the hydrolysis of organic silicate and epoxy compounds, respectively. The silanol is bonded to the alkoxy group of the epoxy compound, and the epoxy group is bonded to the mercapto group of the cross-linked coating, thereby effectively coating the magnetic polymer-based ball and avoiding the loss and loss of the magnetic substance.
[0020] In certain embodiments, the organic silicate is selected from one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate and butyl orthosilicate.
[0021] In some specific embodiments, it is methyl orthosilicate.
[0022] In certain specific embodiments, the mass volume ratio of the magnetic polymer-based spheres to the organic silicate is 1 g: (0.5-5) mL.
[0023] In some more specific embodiments, the ratio may be 1 g: (0.5-2) mL, 1 g: (1-3.2) mL, or 1 g: (3-5) mL. In one example, the ratio may be 1 g: 0.7 mL or 1 g: 1.2 mL.
[0024] In certain embodiments, the epoxy compound is selected from one or more of γ-glycidyloxypropyltrimethoxysilane (KH560), 1,4-butanediol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether and ethylene glycol diglycidyl ether. The applicant has screened epoxy compounds and used KH570 and organic silicate to form a coating of magnetic polymer-based balls. It was found that it is necessary to introduce epoxy groups by polymerization, and the preparation steps are many and cumbersome. In addition, the modified epoxy group configuration is uncontrollable and the number is low, which leads to easy loss of magnetic materials and is not conducive to the subsequent increase in the adsorption of macromolecules.
[0025] In certain specific embodiments, it is γ-glycidyloxypropyltrimethoxysilane (KH560).
[0026] In certain specific embodiments, the mass volume ratio of the magnetic polymer-based sphere to the epoxy compound is 1 g: (0.5-10) mL.
[0027] In some more specific embodiments, the ratio may be 1 g: (0.5-3) mL, 1 g: (1-6) mL, or 1 g: (5-10) mL. In one example, the ratio is 1 g: 1 mL or 1 g: 1.5 mL.
[0028] In certain embodiments, the magnetic polymer-based sphere includes a polymer core and a magnetic material coated on the outer surface of the polymer core.
[0029] In certain specific embodiments, the polymer core is selected from one or more of polystyrene microspheres, polymethyl methacrylate microspheres, polyglycidyl methacrylate microspheres, polylactic acid microspheres and polystyrene-divinylbenzene microspheres. Preferably, the polymer core is polystyrene microspheres.
[0030] In some specific embodiments, the particle size of the polymer core is 1-50 μm, more preferably 1-20 μm, even more preferably 1-10 μm, further specifically 1 μm, 2 μm, 3 μm, 5 μm, 7 μm or 9 μm, such as 2.6 μm.
[0031] In some specific embodiments, the magnetic material is selected from one or both of ferric salts or ferrous salts. Preferably, the magnetic material is selected from ferrous salts and / or ferric salts. The ferrous salt is selected from ferrous chloride; the ferric salt is selected from ferric chloride.
[0032] In some specific embodiments, the preparation method of the magnetic polymer-based spheres is: nitrifying the polymer core to obtain nitrated microspheres; reacting the nitrated microspheres, magnetic materials and precipitants to obtain the magnetic polymer-based spheres. The present application improves hydrophilicity through nitrification.
[0033] Preferably, the magnetic material is selected from ferrous salts and / or ferric salts. The ferrous salt is ferrous chloride. The ferric salt is ferric chloride.
[0034] Preferably, the mass ratio of the nitrated microspheres to the ferrous salt is 1:(0.5-5). More preferably, it is 1:(0.5-2). In one embodiment, it is 1:1.35.
[0035] Preferably, the mass ratio of the nitrated microspheres to the iron salt is 1:(0.5-5). More preferably, it is 1:(0.5-2). In a certain embodiment, it is 1:0.62.
[0036] Preferably, the precipitant is selected from alkaline substances. More preferably, the alkaline substance is ammonia water.
[0037] Preferably, the reaction temperature is 60-100° C. More preferably, it can be 50-70° C., or 60-80° C., or 70-100° C., such as 80° C.
[0038] More preferably, the reaction time is 2 to 10 hours, further preferably, it can be 2 to 7 hours, or 5 to 8 hours, or 6 to 10 hours, such as 3 hours.
[0039] Preferably, the polymer core is obtained by dispersion polymerization, which comprises the following steps: reacting a mixed polymerization monomer, an initiator and a stabilizer in a solvent system to obtain a polymer core.
[0040] More preferably, the polymerizable monomer is styrene.
[0041] More preferably, the initiator is an azo initiator, and further preferably, it is azobisisobutyronitrile.
[0042] More preferably, the mass ratio of the initiator to the polymerization monomer is (0.5-30):100, or (0.5-10):100, or (0.5-5):100, or (8-30):100, such as 0.6:30.
[0043] More preferably, the stabilizer is polyvinyl pyrrolidone (PVP), preferably K30.
[0044] More preferably, the mass ratio of the stabilizer to the polymerizable monomer is (1-30):100, or (1-18):100, or (8-25):100, or (17-30):100, such as 9:30.
[0045] More preferably, the solvent system is an alcohol solution, and further preferably, an ethanol aqueous solution, wherein the concentration of the ethanol aqueous solution is 60% to 90% (v / v).
[0046] More preferably, the reaction temperature is 50-100° C. Further preferably, it can be 50-70° C., or 60-80° C., or 70-100° C., such as 80° C.
[0047] More preferably, the reaction time is 1 to 48 hours. Further preferably, it can be 1 to 24 hours, or 20 to 35 hours, or 30 to 48 hours, such as 6 hours.
[0048] The second invention of the present invention protects the method for preparing the magnetic microspheres as described above, comprising the following steps:
[0049] 1) in a protective atmosphere, reacting a magnetic polymer-based ball, an organic silicate and an epoxy compound in a first solvent under the action of a precipitant to obtain a magnetic polymer-based ball coated with a silicon oxide functional coating;
[0050] 2) In a protective atmosphere, the magnetic polymer-based spheres coated with the silicon oxide functional coating react with mercapto acid in a second solvent to obtain the cross-linked hydrophilic coating magnetic microspheres.
[0051] In certain embodiments, the organic silicate is selected from one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate and butyl orthosilicate.
[0052] In certain embodiments, in step 1), the mass volume ratio of the magnetic polymer-based sphere to the organosilicate is 1 g: (0.5-5) mL.
[0053] In some specific embodiments, the ratio may be 1 g: (0.5-2) mL, 1 g: (1-3.2) mL, or 1 g: (3-5) mL. In one example, the ratio is 1 g: 0.7 mL.
[0054] In certain embodiments, the epoxy compound is selected from one or more of γ-glycidyloxypropyltrimethoxysilane (KH560), 1,4-butanediol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether and ethylene glycol diglycidyl ether.
[0055] In certain specific embodiments, the epoxy compound is selected from γ-glycidyloxypropyltrimethoxysilane (KH560).
[0056] In certain embodiments, in step 1), the mass volume ratio of the magnetic polymer-based spheres to the epoxy compound is 1 g: (0.5-10) mL.
[0057] In some specific embodiments, the mass-to-volume ratio may be 1 g:(0.5-2) mL, 1 g:(1-3.2) mL, or 1 g:(3-10) mL, such as 1 g:1 mL.
[0058] In certain embodiments, in step 1), the precipitant is preferably an alkaline substance, preferably aqueous ammonia.
[0059] In some specific embodiments, the mass concentration of the ammonia water can be 1-20wt%, 1-10wt%, 8-15wt%, or 13-20wt%, such as 10wt%.
[0060] In certain embodiments, in step 1), the volume ratio of the epoxy compound to the precipitant is 1:(1-10).
[0061] In some specific embodiments, the volume ratio can be 1:(1-5), or 1:(3-8), or 1:(7-10), such as 1:1.
[0062] In certain embodiments, in step 1), the reaction temperature is 20-100°C.
[0063] In certain embodiments, the temperature may be 50-100°C, 70-90°C, 20-60°C, or 50°C.
[0064] In certain embodiments, in step 1), the reaction time is 1 to 48 hours.
[0065] In some embodiments, the time may be 1 to 20 hours, 4 to 16 hours, 15 to 32 hours, or 30 to 48 hours, such as 6 hours.
[0066] In certain embodiments, in step 2), the mercapto acid is selected from one or more combinations of mercaptopropionic acid, 2,3-dimercaptobutyric acid and 2,3-dimercaptosuccinic acid.
[0067] In certain embodiments, in step 2), the mass ratio of the magnetic polymer-based spheres coated with the silicon oxide functional coating to the mercapto acid is (1-10):1. In a certain example, it is 10:8 or 10:5.
[0068] In some specific embodiments, the mass ratio can be (1-5):1, (4-8):1, or (7-10):1, such as 10:8.
[0069] In certain embodiments, step 2) further comprises adding a catalyst, wherein the catalyst is selected from alkaline compounds, and the alkaline compound is used to adjust the pH value of the reaction system to be above 10.
[0070] In certain specific embodiments, the catalyst is selected from one or more of sodium carbonate, potassium carbonate, sodium hydroxide and triethylamine.
[0071] In certain embodiments, in step 2), the reaction temperature is 30-100°C.
[0072] In some specific embodiments, the temperature may be 30-70°C, 40-80°C, or 75-100°C, such as 50°C.
[0073] In certain embodiments, in step 2), the reaction time is 1 to 48 hours.
[0074] In certain specific embodiments, the reaction time can be 1 to 24 hours, 10 to 31 hours, or 30 to 48 hours, such as 15 hours.
[0075] In certain embodiments, the reaction further includes post-treatment, wherein the post-treatment includes cooling and washing. The solvent used for the washing is alcohol.
[0076] In certain embodiments, in step 1) or step 2), the protective atmosphere may be any protective atmosphere well known to those skilled in the art without any particular limitation, and nitrogen is preferred in the present invention.
[0077] In some embodiments, the cross-linked hydrophilic coating magnetic microspheres are further modified with functional groups, which can be performed using common methods in the art.
[0078] In certain specific embodiments, the functional group is selected from carboxyl, hydroxyl or amino.
[0079] The third invention of the present invention protects the use of the magnetic microspheres as described above in the preparation of diagnostic reagents.
[0080] The fourth invention of the present invention protects a diagnostic reagent, including the magnetic microspheres as described above or the magnetic microspheres obtained by the preparation method as described above.
[0081] The present invention utilizes the "click chemistry-like characteristics" of epoxy and thiol reactions, such as fast reaction speed, mild conditions, and high selectivity, to effectively coat the surface of magnetic polymer-based balls without any auxiliary conditions, greatly improving the chemical stability of magnetic polymer-based balls and effectively reducing non-specific adsorption of proteins, providing a new exploration direction for cross-linked hydrophilic coating magnetic microspheres. The present invention relates to production raw materials that are simple and easy to obtain, low in cost, and easy to industrialize. The product can be used as a biological raw material in the fields of immunoassay, chemiluminescence, etc., greatly reducing the non-specific adsorption of chemiluminescent magnetic beads, making them have a lower background value and a higher signal-to-noise ratio, and showing better detection sensitivity.
[0082] Compared with the prior art, the present invention has the following beneficial effects:
[0083] 1) The cross-linked coating of the magnetic microspheres provided by the present invention can not only effectively cover the surface of the magnetic microspheres tightly to prevent the loss and leakage of magnetic substances, but also the generated cross-linked coating can produce secondary hydroxyl groups and thioethers, which significantly increase the hydrophilicity of the surface of the magnetic microspheres, effectively reduce the nonspecific adsorption of proteins by the magnetic microspheres, make them have a lower background value and a higher signal-to-noise ratio, and improve the luminescence sensitivity.
[0084] 2) The present invention uses epoxy compounds and organic silicates to form a silane oxide functional coating, which can load more epoxy groups, and is more conducive to the subsequent cross-linking of mercapto and epoxy groups to form a cross-linked coating, thereby preventing the loss or loss of magnetic substances. The magnetic response time T 50 Less than 30 seconds, enabling rapid separation and detection.
[0085] 3) When the cross-linked hydrophilic coating magnetic microspheres of the present invention are subjected to chemiluminescence performance detection, a lower background value is shown for proteins, indicating that they have non-specific adsorption for proteins. When used for detecting proteins, they have the advantages of high sensitivity and strong specificity. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 The electron microscope images of the cross-linked hydrophilic coating magnetic microspheres obtained in Example 1 of the present application are shown in Figure 1. A is an electron microscope image of the magnetic polymer-based spheres, with a scale of 0.5 μm; and B is an electron microscope image of the cross-linked hydrophilic coating magnetic microspheres, with a scale of 0.5 μm.
[0087] Figure 2 This is a graph showing the magnetic properties test results of the cross-linked hydrophilic coated magnetic microspheres obtained in Example 1 and Comparative Example 1 of the present application.
[0088] Figure 3 This is a schematic diagram of the cross-linked hydrophilic coated magnetic microspheres obtained in Example 1 of the present application.
[0089] Figure 4 This is a schematic diagram of the cross-linked hydrophilic coated magnetic microspheres obtained in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0090] The present invention will be further described below in conjunction with specific embodiments. The following are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto.
[0091] The raw materials of the following examples of the present application are not particularly limited and are all commercially available.
[0092] The following embodiments of the present application use polystyrene as the polymer core, but are not limited to polystyrene cores. Polymethyl methacrylate microspheres, polyglycidyl methacrylate microspheres, polylactic acid microspheres and polystyrene-divinylbenzene microspheres can also be used as polymer cores to implement the technical solution of the present application and achieve the technical effects of the present application. The preparation method of magnetic polymer-based balls using polystyrene as the polymer core comprises the following steps:
[0093] 1) Take 30g of styrene (as a polymerization monomer) and 9g of PVP (as a stabilizer, k30) and evenly disperse them in 250mL of 90% (V / V) ethanol solution and add them to a 500mL three-necked flask. Heat to 80°C under mechanical stirring, then add 0.6g of azobisisobutyronitrile (AIBN, as an initiator) and continue to react for 6h at this temperature. The product is washed with centrifugal alcohol and water and dried to obtain a polymer core with a particle size of 2.6±0.1μm.
[0094] 2) Weigh 10g of the polymer core into a 250mL three-necked flask, add 150mL of sulfuric acid / nitric acid mixture (v / v), and heat to 50℃ for nitration treatment for 4h under mechanical stirring. After the reaction, put the feed liquid into crushed ice and cool it naturally to room temperature, centrifuge and wash until the supernatant is neutral, and then separate and dry the product to obtain nitrated microspheres.
[0095] 3) Weigh 10g of nitrated microspheres and disperse them evenly in 150mL of deionized water. Add 13.5g of FeCl 3 6H 2 O, 6.2 gFeCl 2 ·4H 2 O solution, in N 2 The mixture was stirred in an atmosphere for 1 hour, and then 200 mL of 10 wt% ammonia water was introduced thereto. The reaction was continued at 80° C. for 3 hours. After magnetic adsorption and ultrasonic washing, magnetic polymer-based spheres were obtained.
[0096] Example 1
[0097] This embodiment 1 provides a cross-linked cross-linked coating magnetic microsphere and a preparation method thereof, such as Figure 3 The schematic diagram shown includes the following steps:
[0098] 1) Silicon oxide functional coating: 10 g of magnetic polymer-based balls were weighed and evenly dispersed in 400 mL of 80% (v / v) ethanol solution. Then, 7 mL of tetraethyl orthosilicate and 10 mL of KH560 were introduced therein. The mixture was mechanically stirred at 25 °C for 30 min. Then, 15 mL of 10 wt% ammonia water was added. The temperature was raised to 50 °C and the reaction was continued for 6 h. After the product was washed with ethanol and water by magnetic absorption, microspheres coated with silicon oxide functional coating, i.e., epoxy microspheres, were obtained.
[0099] 2) Coating with cross-linked coating: 10 g of epoxy microspheres obtained in step 1) are uniformly dispersed in 500 mL of 40% ethanol solution, 5 g of 2,3-dimercaptosuccinic acid is added thereto, and after stirring and ultrasonicating to dissolve it, NaOH solution is added thereto to adjust the pH to above 10, and the reaction is continued for 15 h. After the reaction is completed, ethanol and water are washed three times respectively, and finally dispersed in deionized water for storage to obtain cross-linked hydrophilic coated magnetic microspheres, which are recorded as C1.
[0100] The cross-linked hydrophilic coated magnetic microspheres obtained in Example 1 were observed using a scanning electron microscope. Figure 1 .in, Figure 1 A is a magnetic polymer base ball. Figure 1 B is the final product obtained in step 2), that is, the cross-linked hydrophilic coated magnetic microspheres obtained after being coated with the silicon oxide functional coating and the cross-linked coating.
[0101] from Figure 1 It can be seen that after epoxy-thiol cross-linking modification, the surface becomes smooth and dense, indicating that there is an obvious coating layer, which can protect the inner magnetic material and the surface functionalization. Among them, the thickness of the silicon oxide functional coating is 50nm, and the thickness of the cross-linking coating is 50nm.
[0102] Example 2
[0103] This embodiment 2 provides a cross-linked cross-linked coating magnetic microsphere and a preparation method thereof, such as Figure 3 The schematic diagram shown includes the following steps:
[0104] 1) Silicon oxide functional coating: 10 g of magnetic polymer-based balls were weighed and evenly dispersed in 400 mL of 80% (v / v) ethanol solution. Then, 12 mL of tetraethyl silicate and 15 mL of KH560 were introduced thereto. The mixture was mechanically stirred at 25 °C for 30 min. Then, 20 mL of 10 wt% ammonia water was added. The temperature was raised to 50 °C and the reaction was continued for 6 h. After the product was washed with ethanol and water by magnetic absorption, microspheres coated with silicon oxide functional coating, i.e., epoxy microspheres, were obtained.
[0105] 2) Coating with cross-linked coating: 10 g of epoxy microspheres obtained in step 1) are uniformly dispersed in 500 mL of 40% ethanol solution, 8 g of 6,8-dimercaptooctanoic acid is added thereto, and after stirring and ultrasonication to dissolve, triethylamine is added dropwise thereto to adjust the pH to above 10, and the reaction is continued for 15 h. After the reaction is completed, ethanol and water are washed three times respectively, and finally dispersed in deionized water for storage to obtain cross-linked hydrophilic coated magnetic microspheres, which are recorded as C2.
[0106] In this embodiment, the thickness of the silicon oxide functional coating is 56 nm, and the thickness of the cross-linked coating is 61 nm.
[0107] Example 3
[0108] The difference between Example 3 and Example 1 is that no alkaline catalyst is used in step 2), and the rest is the same as Example 1.
[0109] 1) Silicon oxide functional coating: 10 g of magnetic polymer-based balls were weighed and evenly dispersed in 400 mL of 80% (v / v) ethanol solution. Then, 7 mL of tetraethyl orthosilicate and 10 mL of KH560 were introduced therein. The mixture was mechanically stirred at 25 °C for 30 min. Then, 15 mL of 10 wt% ammonia water was added. The temperature was raised to 50 °C and the reaction was continued for 6 h. After the product was washed with ethanol and water by magnetic absorption, microspheres coated with silicon oxide functional coating, i.e., epoxy microspheres, were obtained.
[0110] 2) Coating with cross-linked coating: 10 g of epoxy microspheres obtained in step 1) are evenly dispersed in 500 mL of 40% ethanol solution, 5 g of 2,3-dimercaptosuccinic acid is added thereto, and after stirring and ultrasonication until it is dissolved, the reaction is continued for 15 h. After the reaction is completed, ethanol and water are washed three times respectively, and finally dispersed in deionized water for storage to obtain cross-linked hydrophilic coated magnetic microspheres, which are recorded as C3.
[0111] In this embodiment, the thickness of the silicon oxide functional coating is 62 nm, and the thickness of the cross-linked coating is 65 nm.
[0112] Comparative Example 1
[0113] In this comparative example 1, KH570 was used as the epoxy compound to prepare magnetic microspheres. Figure 4 The specific steps are as follows:
[0114] 1) Weigh 10 g of magnetic polymer-based balls and disperse them evenly in 400 mL of 80% (v / v) ethanol solution. Then, introduce 7 mL of tetraethyl silicate and 10 mL of double-bond silane coupling agent (KH570) into the solution and stir mechanically at 25 °C for 30 min. Then, add 15 mL of ammonia water and heat to 50 °C to continue the reaction for 6 h. After the product is washed with ethanol and water by magnetic absorption, microspheres coated with double-bond silane functional coating, i.e., double-bond modified microspheres, are obtained.
[0115] 2) 10 g of the double-bond modified microspheres obtained in step 1) were uniformly dispersed in 500 mL of 40% ethanol solution, 4 g of glycidyl methacrylate, 0.4 g of N,N-methylenebisacrylamide, and 0.04 g of AIBN were uniformly dispersed in N 2 The mixture was dispersed and stirred for 30 minutes under an atmosphere, and then the temperature was raised to 80°C for reaction for 8 hours; 5 g of 2,3-dimercaptosuccinic acid was added thereto, and after stirring and ultrasonication for dissolution, NaOH solution was added dropwise thereto to adjust the pH to above 10, and the reaction was continued for 15 hours. After the reaction was completed, the mixture was washed with ethanol and water for 3 times respectively, and finally dispersed in deionized water for storage to obtain magnetic microspheres, which were recorded as D1.
[0116] Comparative Example 2
[0117] Comparative Example 2 is to prepare magnetic microspheres by adding only epoxy compounds without adding organosilicate, including the following:
[0118] 1) 10 g of magnetic polymer-based spheres were weighed and uniformly dispersed in 400 mL of 80% (v / v) ethanol solution, and then 12 mL of KH560 was introduced therein, and mechanical stirring was performed at 25 °C for 30 min. Then 15 mL of 10 wt% ammonia water was added, and the temperature was raised to 50 °C and the reaction was continued for 6 h. After the product was washed with ethanol and water magnetic absorption, microspheres coated with silicon oxide functional coating, i.e., epoxy-based microspheres, were obtained.
[0119] 2) 10 g of the epoxy microspheres obtained in step 1) were uniformly dispersed in 500 mL of 40% ethanol solution, 5 g of 2,3-dimercaptosuccinic acid was added thereto, and after stirring and ultrasonicating to dissolve it, NaOH solution was added dropwise thereto to adjust the pH to above 10, and the reaction was continued for 15 h. After the reaction was completed, ethanol and water were washed three times respectively, and finally dispersed in deionized water for storage to obtain magnetic microspheres, which were recorded as D2.
[0120] Determination of the number of epoxy groups: The epoxy value of the epoxy microspheres obtained in step 1) of Example 1 and Comparative Examples 1 and 2 was measured. The results are shown in Table 1.
[0121] The epoxy value content on the surface of epoxy microspheres was determined by titration:
[0122] Instruments: 250mL conical flask, 10mL pipette, basic burette
[0123] Reagents: hydrochloric acid acetone solution (concentrated hydrochloric acid content 2.5v / v%, prepared before use), 0.1% methyl red indicator, 0.1M NaOH standard solution.
[0124] Steps: Weigh 0.1 g of the epoxy microspheres of Example 1, Comparative Example 1, and Comparative Example 2 into a 250 mL conical flask, pipette 20 mL of hydrochloric acid acetone solution into the conical flask and mix evenly, and place it in the reaction for 30 minutes, then add 1 to 2 drops of methyl red indicator, and titrate with 0.1 M NaOH solution until the color of the solution changes from red to yellow and remains unchanged for about 30 seconds, and perform a blank experiment.
[0125]
[0126] V 0 is the volume of NaOH consumed by the blank, mL; V is the volume of NaOH consumed by the sample, mL; C is the concentration of the NaOH solution, mol / L; m is the mass of the sample, g.
[0127] Epoxy means epoxy value. The higher the epoxy value, the higher the epoxy group content.
[0128] Table 1
[0129]
[0130] As can be seen from Table 1, compared with Comparative Example 2 in which no organic acid ester is added, the addition of organic silicate in the present application helps to modify more epoxy groups on the surface of the epoxy microspheres, and its epoxy value is more than 3 times that of Comparative Example 2; the epoxy value of the epoxy microspheres in Example 1 is more than 11 times that of Comparative Example 1, indicating that the organic acid ester and the epoxy compound in the present application synergistically increase the number of epoxy group modifications.
[0131] The cross-linked hydrophilic coated magnetic microspheres of Examples 1-3 and the final product magnetic microspheres obtained in Comparative Examples 1 and 2 were tested for chemiluminescence properties using an enzymatic method. The specific operation is as follows:
[0132] 1. Coupling:
[0133] A TSH antibody solution with a concentration of 1 μg / μL and an EDC solution with a concentration of 10 mg / mL were prepared using a reaction buffer (0.1 mM MES, pH 6.0).
[0134] 1) Take 2 mL (10 mg / mL) of the magnetic microspheres of Examples 1 to 3 and Comparative Examples 1 and 2, centrifuge and discard the supernatant, then add 1 mL of deionized water to wash for 1 min, centrifuge and discard the supernatant; then add 1 mL of reaction buffer to wash for 1 min, centrifuge and discard the supernatant.
[0135] 2) Add 100 mL of 10 mg / mL EDC solution and 100 μL of reaction buffer and activate for 30 min.
[0136] 3) Then add 1 mL of 1 μg / μL TSH solution, place on a rotating mixer, incubate at room temperature for 16 h, and keep at 2-8°C for later use to obtain a coupled sample.
[0137] 2. Test:
[0138] Each coupled sample obtained in step 1 was fixed to the primary antibody anti-TSH monoclonal antibody (HyTest, Ltd, clone: 10C7) as follows:
[0139] 10 μg of the above-mentioned coupled sample was reacted with human serum TSH antigen samples (50 μL) at various concentrations at 37°C for 20 min, magnetically separated and washed three times with TB buffer, and then reacted with secondary antibodies labeled with alkaline phosphatase (ALP) (HyTest, Ltd, clone: 105E8). After adding substrate solution (AMPPD), the chemiluminescence amount was measured. The luminescence value detection results are shown in Table 2.
[0140] In Table 2, TC1, TC3, TC5 and TC7 respectively represent the concentrations of the antigen, TC1 represents an antigen concentration of 0 mIU / L, TC3 represents an antigen concentration of 0.2 mIU / L, TC5 represents an antigen concentration of 20 mIU / L and TC7 represents an antigen concentration of 85 mIU / L.
[0141] The luminescence value of TC1 is also the background value. The lower the luminescence value, the lower the background value. The background value is one of the important parameters for evaluating the specificity and sensitivity of chemiluminescence detection. A low background value indicates low system noise, which can improve detection specificity and sensitivity. S / N stands for the signal-to-noise ratio, which is calculated by TC3 / TC1 and is used to evaluate sensitivity.
[0142] Table 2
[0143]
[0144] It can be seen from Table 2 that when the antigen concentration is 0mIU / L, the cross-linked hydrophilic coated magnetic microspheres of the present application show a lower background value, while the background values of Comparative Examples 1 and 2 are both over 10,000, indicating that the cross-linked hydrophilic coated magnetic microspheres of the present application have nonspecific adsorption to proteins, and when used to detect proteins, they have the advantages of high sensitivity and strong specificity.
[0145] Magnetic properties test experiment:
[0146] The cross-linked hydrophilic coating magnetic microspheres obtained in Example 1 and the magnetic microspheres obtained in Comparative Example 1 were subjected to a magnetic performance test, and the specific operation was as follows:
[0147] Accurately weigh 0.25g of each magnetic bead sample to be tested, add it to a 250mL reagent bottle, adjust the sample concentration to 1mg / mL with deionized water, shake well and set aside; turn on the detection instrument (Sepmag A200), set the relevant test parameters and perform T 50 Test. Before the test, hold the reagent bottle with both hands, turn it upside down 5 times to ensure that the magnetic beads are dispersed and suspended without precipitation, let it stand horizontally for 1 minute, and then put it into the instrument for testing. Set the relevant test parameters as follows: open the software, click Measures to select ProcessMonitoring, enter the sample name in Process Name, select 250mL in Position Volume, click Add to join the test queue and wait for the test, and click Start to start the test.
[0148] T 50 , also known as magnetic response time, represents the time required for the magnetic properties of the magnetic microsphere suspension to reach 50% of its maximum value (saturation magnetization intensity) from 0. It is an important parameter for measuring the magnetic properties of magnetic microspheres. 50 The shorter or smaller it is, the shorter the time required for the magnetic microspheres to reach half of the maximum magnetization intensity, indicating that the magnetic properties are better.
[0149] Results Figure 2 C1 is the magnetic property of Example 1, D1 is the magnetic property of Comparative Example 1, and D3 is the magnetic property of Comparative Example 2. Figure 2It can be seen that the magnetic response time of the cross-linked hydrophilic coating magnetic microspheres obtained in Example 1 is shorter, only 20s, and the magnetic properties are better; while the magnetic microspheres obtained in Comparative Example 2 without adding organic silicate have a magnetic response time of 45s; and the magnetic microspheres obtained by using KH570 have a magnetic response time of 30s; This shows that the silicon oxide functional coating formed by epoxy compounds and organic silicate can prevent the loss and loss of magnetic substances.
Claims
1. A cross-linked hydrophilic coated magnetic microsphere, characterized in that: include: A magnetic polymer-based ball, comprising a polymer core and a magnetic material coated on the outer surface of the polymer core; A silicon oxide functional coating is coated on the outer surface of the magnetic polymer-based ball, wherein the raw materials of the silicon oxide functional coating include organic silicate and epoxy compound; A cross-linked coating is coated on the outer surface of the silicon oxide functional coating, wherein the raw material of the cross-linked coating includes mercapto acid; The polymer core is selected from one or more of polystyrene microspheres, polymethyl methacrylate microspheres, polyglycidyl methacrylate microspheres, polylactic acid microspheres and polystyrene-divinylbenzene microspheres; The mercapto acid is selected from one or both of 2,3-dimercaptosuccinic acid and 6,8-dimercaptooctanoic acid.
2. The cross-linked hydrophilic coated magnetic microspheres according to claim 1, characterized in that: The organic silicate is selected from one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate and butyl orthosilicate; and / or, the epoxy compound is selected from one or more of γ-glycidyloxypropyltrimethoxysilane, 1,4-butanediol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether and ethylene glycol diglycidyl ether; And / or, the raw material of the magnetic material is selected from one or both of trivalent iron salts and divalent iron salts.
3. The cross-linked hydrophilic coated magnetic microspheres according to claim 2, characterized in that: The mass volume ratio of the magnetic polymer-based ball to the epoxy compound is 1 g: (0.5-10) mL; and / or, the mass volume ratio of the magnetic polymer-based sphere to the organic silicate is 1 g: (0.5-5) mL; And / or, the mass ratio of the magnetic polymer-based ball to the mercapto acid is 1:(0.5-20); And / or, the particle size of the polymer core is 1-50 μm.
4. The cross-linked hydrophilic coated magnetic microspheres according to claim 2, characterized in that: The preparation method of the magnetic polymer-based ball comprises: nitrating the polymer core to obtain nitrated microspheres; reacting the nitrated microspheres, magnetic materials and a precipitant to obtain the magnetic polymer-based ball.
5. The cross-linked hydrophilic coated magnetic microspheres as claimed in claim 4, characterized in that: The mass ratio of the nitrated microspheres to the magnetic material is 1:(0.5-5); And / or, the precipitant is selected from alkaline substances; And / or, the reaction temperature is 60-100°C.
6. The cross-linked hydrophilic coated magnetic microspheres as claimed in claim 5, characterized in that: The alkaline substance is aqueous ammonia.
7. The method for preparing cross-linked hydrophilic coated magnetic microspheres according to any one of claims 1 to 6, characterized in that: The steps include: 1) In a protective atmosphere, a magnetic polymer-based ball, an organic silicate and an epoxy compound react in a first solvent under the action of a precipitant to obtain a magnetic polymer-based ball coated with a silicon oxide functional coating; 2) In a protective atmosphere, the magnetic polymer-based spheres coated with the silicon oxide functional coating react with mercapto acid in a second solvent to obtain the cross-linked hydrophilic coating magnetic microspheres.
8. The preparation method according to claim 7, characterized in that: In step 1), the reaction temperature is 20-100°C; And / or, in step 1), the reaction time is 1 to 48 hours; And / or, in step 1), the first solvent is selected from one or two of ethanol and water; And / or, in step 1), the precipitant is selected from alkaline substances.
9. The preparation method according to claim 8, characterized in that: The alkaline substance is aqueous ammonia.
10. The preparation method according to claim 7, characterized in that: Step 2) further comprises adding a catalyst, wherein the catalyst is selected from one or more of sodium hydroxide, sodium carbonate, potassium carbonate and triethylamine; And / or, in step 2), the second solvent is selected from one or two of ethanol and water; And / or, in step 2), the reaction temperature is 30-100°C; And / or, in step 2), the reaction time is 1 to 48 hours.
11. Use of the cross-linked hydrophilic coated magnetic microspheres according to any one of claims 1 to 6 in the preparation of diagnostic reagents.
12. A diagnostic reagent, characterized in that The invention comprises the cross-linked hydrophilic coating magnetic microspheres as claimed in any one of claims 1 to 6 or the cross-linked hydrophilic coating magnetic microspheres obtained by the preparation method as claimed in any one of claims 7 to 10.
Citation Information
Patent Citations
Method for preparing bionic coating through crosslinking of epoxy group and mercapto group
CN105288731A
Polymer magnetic sphere material with low luminous background and preparation method thereof
CN117417575A
Magnetic bead, ligand-binding bead, method for detecting or separating target substance, and method for producing the magnetic bead
US20160069871A1